2015
DOI: 10.15171/ijhpm.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

An Instrumental Variable Probit (IVP) analysis on depressed mood in Korea: the impact of gender differences and other socio-economic factors

Abstract: Background: Depression is a mental health state whose frequency has been increasing in modern societies. It imposes a great burden, because of the strong impact on people's quality of life and happiness. Depression can be reliably diagnosed and treated in primary care: if more people could get effective treatments earlier, the costs related to depression would be reversed. The aim of this study was to examine the influence of socio-economic factors and gender on depressed mood, focusing on Korea. In fact, in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
1
4
0
1
Order By: Relevance
“…This is one of the first studies to successfully provide statistical evidence of an association between gender disparities in psychiatric disorders and social inequalities at a global level. These results contribute to the growing evidence that social inequality has an independent effect on population-specific depressive disorders 24 , 48 . This study was enhanced by a multi-faceted approach to the matter of inequality that utilized both the United Nations’ definition of inequality and measures of inequality such that gender inequality could be captured more precisely.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This is one of the first studies to successfully provide statistical evidence of an association between gender disparities in psychiatric disorders and social inequalities at a global level. These results contribute to the growing evidence that social inequality has an independent effect on population-specific depressive disorders 24 , 48 . This study was enhanced by a multi-faceted approach to the matter of inequality that utilized both the United Nations’ definition of inequality and measures of inequality such that gender inequality could be captured more precisely.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies that have not adequately addressed this problem typically analyzed the data using gender (Notes 2) as a dichotomous variable. Moreover, the scope of many studies has been limited to specific countries 24 , 48 51 . For example, one study that indicated the potential correlation between the wage gap and gender disparities in mood disorders was limited to the United States and only used the wage gap to measure gender inequality 24 .…”
Section: Introductionmentioning
confidence: 99%
“…By way of comparison, gender-dependent differences in depression scores may be considered given that the participants of the previous study were exclusively women. However, not only is there a higher prevalence of depression in women than men (Parker & Brotchie, 2010), but a study on gender differences in depression conducted with about 6,700 Koreans also verified that women are also more vulnerable to it (Gitto et al, 2015). From these results, it can be inferred that the level of depression perceived by the participants in this study is higher than that in the previous study that only sampled women.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sabia and Rees ( 2011 ) show that migraine is related to individual heterogeneity in the form of personality not to educational attainment. Gitto et al ( 2015 ) use high education as an instrumental variable in the analysis of depressed mood in Korea.…”
Section: Methodsmentioning
confidence: 99%